The Qx-coder - Slattery, M. J.; Mitchell, J. L. (IBM journal of research and development, 1998)
The IBM Adaptive Bilevel Image Compression (ABIC) algorithm depends upon the hardware-optimized Q-coder. The Joint Bi-level Image Experts Group (JBIG) settled upon a software-optimized QM-coder. This paper explores the incompatibilities of the hardware- and software-optimized binary arithmetic coding conventions and reports on the solution that allowed a merged Qx-coder in hardware. A unique hardware solution is presented for the termination of the JBIG data stream (CLEARBITS). The probability estimation is presented in a common format. Detailed flowcharts are included in the Appendix. An ASIC core is available that supports both the ABIC and JBIG bilevel data compression standards using this merged Qx-coder.